Stress, Coping, Self-efficacy and Birth Satisfaction among Low-risk Pregnant Women: A Cross-sectional Study - KK Ajini; N Rajeev Kumar; JS Ajith Prasad (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Pregnant women worry about their physical changes, child delivery and impending parenthood. Wide range of psychological, biological and social factors influence emotional wellbeing during pregnancy which can be described by the extent of birth anxiety, self-efficacy and psychosocial adaptations. The factors like coping and self-efficacy help to overcome the stress and provide better birth satisfaction resulting in good mother and infant bonding. Aim: To know stress levels among low-risk pregnant women and to assess the influence of coping and self-efficacy of these women on birth satisfaction after delivery. Materials and Methods: A prospective, cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Government Medical College, Thrissur, Kerala, India, from January 2019 to June 2019. Total 188 pregnant women who reached term and without any known risk factors in the current pregnancy were enrolled. Data was collected using proforma and questionnaires by conducting semi-structured interview to measure pregnancy specific stress, coping, self-efficacy and birth satisfaction. Data was analysed using Statistical Package for the Social Sciences (SPSS) software version 16.0. Multiple regression analysis was used for analysing the influence of stress, coping and self-efficacy on birth satisfaction. Results: Study showed that 14.36% of women had high levels of stress. Antenatal women residing at rural areas had high levels of stress than their urban counterparts (p-value=0.004). Employed women had high levels of self-efficacy (p-value=0.038). significant negative correlation was seen between the stress and self-efficacy (r-value=-0.479, p-value<0.00001) Conclusion: Stress do exist even among low-risk pregnant women. Abilities like coping and self-efficacy improves birth satisfaction in women. Birth satisfaction is an important factor in ensuring positive birth experience and respectful maternity care.